Atmospheric methane emissions for Argentina: comparison with TROPOMI satellite measurements - Puliafito, Salvador Enrique (2020)
Methane emissions have very important effect on global radiative forcing. Therefore, reducing these emissions has been proposed as an effective short-term strategy to mitigate global warming, in parallel with reductions in long-lived carbon dioxide (CO2) for long- term temperature stabilizations. In this context, Argentina emits 3645 Gg of CH4 mainly from livestock production, biomass burning and natural gas production. Since 2018, TROPOMI instruments provide global coverage on methane column-average mole fraction of dry air (XCH4), and height profiles of methane concentrations. We compare two available methane inventory: a national (a high resolution of own ellaboration: GEAA) and an international (EDGAR) emissions database with TROPOMI measurements. By performing inverse satellite retrieval we evaluate the ability of remote sensing information to detect possible hotspot methane emissions and compare these results with the two inventories. From these analyzes, we observe that the latitudinal averages of the continental sector increase at a rate of 10 ppb/degree, from south to north, while the maritime sector remains constant. From a temporary perspective, the average monthly concentration amplitude range varies 40 to 50 ppb, with minimum values in March and maximum values in September.